Environmental ethics in biology education: A scoping review of ecological philosophy paradigms in school curriculum development - Jusman Tang; Abdullah Sinring; Syamsu A. Kamaruddin; Fenny Hasanuddin; Sam Hermansyah (Edumaspul: Jurnal Pendidikan, 2025)
The global environmental crisis necessitates a paradigm shift in biology education that integrates environmental ethics and ecological philosophy into school curricula. This study aims to comprehensively examine the implementation of environmental ethics–based biology education through a scoping review approach. The research employed the PRISMA-ScR framework and conducted a systematic search of 68 articles from Scopus and SINTA-indexed journals (Q1, Q2, Q3, and SINTA 1, 2, 3) published between 2015 and 2025. The analysis identified three major domains: (1) the integration of environmental ethics in the biology curriculum, encompassing anthropocentric, biocentric, and ecocentric approaches; (2) ecological philosophy as a paradigm that cultivates moral awareness and ecological responsibility through experiential and project-based learning; and (3) the implementation of ecology-oriented curricula, which enhances students’ environmental literacy, critical thinking, and pro-environmental behavior. The findings reveal research gaps related to long-term impact assessment and the development of holistic evaluation models. This study recommends the systematic integration of philosophical environmental values into the biology curriculum to foster a generation with deep ecological awareness and strong commitments to sustainability. A transdisciplinary approach that combines ecological knowledge, moral values, and local wisdom is essential for transforming biology education toward a sustainable ecological paradigm.